Contrapontando: um roteiro de integração de competências para o ensino-aprendizagem da notação musical digital - RODRIGUES, Rodrigo Gabriel Ramos (Universidade Federal do Pará, 2023)
This work presents the results of research carried out within the scope of the Postgraduate Program in Creativity and Innovation in Higher Education Methodologies at the Federal University of Pará (UFPA) aimed at the development and evaluation of an integration roadmap to enhance the teaching-learning process of Digital Musical Notation (DMN) for Music teachers in higher education. For this, we activated our experience as teachers of the Bachelor's Degree in Music at the Carlos Gomes State Institute (IECG), which was configured as the locus of the research. The resulting Educational Process (EP) from the research was titled "COUNTERPOINTING", and consists of a proposed teaching-learning journey made available in digital format, which systematizes a process of integrating digital and musical skills, based on the approximation of levels/layers previously defined by frameworks (CARRETERO GOMEZ, 2017; REDECKER, 2018) and musical theories, such as Swanwick's (1994, 1999, 2003, 2014, 2021). The construction of this research took place in six phases. In the first, we focused on characterizing the locus of our professional activity, from which it was possible to understand the structure of the IECG, the Bachelor's course, and the role of the Music Publishing disciplines within this course. The second phase was dedicated to mapping and analyzing six score editing programs, identifying differences and similarities between them. The third phase consisted of surveying information about the ownership and use of technologies among IECG students, reaching a sample of 30% of the student body of the institution. The fourth phase was for conceptualizing and discussing the premises of what we understand as DMN. In the fifth phase, we evaluated the content of the first version of the Educational Process (EP). The suggestions, recommendations, and comments received from the four evaluators allowed significant improvements to the EP, as well as a better understanding of the relevance of its proposition. The sixth and final phase, therefore, was dedicated to the conception and development of the final version of the EP, involving a design professional and text review. Among the results and contributions of this research, we highlight that the construction of the roadmap will enable teachers to expand the knowledge of their musician students, assisting in the study of other subjects and enhancing learning autonomy through technology. We believe that the development of this EP already benefits both the IECG community and any other teacher who is interested in promoting the development of Digital Musical Notation.